Survival of patients with skin melanoma in Europe increases further: Results of the EUROCARE-5 study. Issue 15 (October 2015) - Crocetti, Emanuele; Mallone, Sandra; Robsahm, Trude Eid; Gavin, Anna; Agius, Domenic; Ardanaz, Eva; Lopez, Maria-Dolores Chirlaque; Innos, Kaire; Minicozzi, Pamela; Borgognoni, Lorenzo; Pierannunzio, Daniela; Eisemann, Nora; et al.
Abstract: Background: In Europe skin melanoma (SM) survival has increased over time. The aims were to evaluate recent trends and differences between countries and regions of Europe. Methods: Relative survival (RS) estimates and geographical comparisons were based on 241, 485 patients aged 15 years and over with a diagnosis of invasive SM in Europe (2000–2007). Survival time trends during 1999–2007 were estimated using the period approach, for 213, 101 patients. Age, gender, sub-sites and morphology subgroups were considered. Results: In European patients, estimated 5-year RS was 83% (95% confidence interval, CI 83–84%). The highest values were found for patients resident in Northern (88%; 87–88%) and Central (88%; 87–88%) Europe, followed by Ireland and United Kingdom (UK) (86%; 85–86%) and Southern Europe (83%; 82–83%). The lowest survival was in Eastern Europe (74%; 74–75%). Within regions the intercountry absolute difference in percentage points of RS varied from 4% (North) to 34% (East). RS decreased markedly with patients' age and was higher in women than men. Differences according to SM morphology and skin sub-sites also emerged. Survival has slightly increased from 1999 to 2007, with a small improvement in Northern and the most pronounced improvement in Eastern Europe. Discussion: SM survival is high and still increasing in European patients. The gap between Northern and Southern and especially Eastern European countries, although still present, diminished over time. Differences in stage distribution at diagnosis may explain most of the geographical differences. However, part of the improvement in survival may be attributed to overdiagnosis from early diagnosis practices.